Small Cell Cervical Carcinoma in Pregnancy: Therapeutic Options for an Aggressive Cancer Diagnosis - Alyssa Savelli Binsted; Zeinab Kassem; David Le; Margarita de Veciana (Thieme Medical Publishers, Inc., 2024)
Neuroendocrine small cell cervical carcinoma is an aggressive cancer which accounts for approximately 1 to 3% of all cervical neoplasms. Therapy must be altered in pregnancy to optimize maternal-fetal outcomes. A 39-year-old woman presented for a routine prenatal visit and was noted to have a grossly abnormal cervix. Cervical biopsies confirmed small cell carcinoma. At 19 weeks' gestation, chemotherapy was initiated. The patient delivered at 34 weeks' gestation to initiate radiation therapy. Six months later, she was diagnosed with metastatic disease and died from cancer complications. In pregnancy, treatment modalities for small cell cervical carcinoma are based on the patient's gestational age at diagnosis. While aggressive early treatment is preferred, platinum-based chemotherapy can be initiated in the second trimester and radiation therapy delayed until delivery. Small cell cervical carcinoma complicating pregnancy requires aggressive treatment. Chemotherapy in the second trimester with planned delayed radiation therapy, may optimize fetal outcomes.